1987
DOI: 10.1136/sti.63.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Response of pharyngeal gonorrhoea to single dose penicillin treatment.

Abstract: SUMMARY The prevalence of gonococcal infection of the pharynx in 205 women, 331 heterosexual men, and 11 homosexual men with gonorrhoea was 6-8%, 4.2% and 27.3% respectively. In only one patient, a heterosexual man, was the pharynx the sole site of infection. Throat symptoms were found in 7% ofwomen, 21% of heterosexual men, and none of the homosexual men. Orogenital contact was reported by 29% of women, 36% of heterosexual men, and all the homosexual men. A single intramuscular dose of 1.8 g Bicillin (procain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…37, 38 The data on screening for women for extra-genital infection is mixed. Studies conducted in the 1970s and 1980s found that among women with genital tract infections with N. gonorrhoeae, approximately 10–25% had concurrent pharyngeal gonorrhea, 3336, 4042 and nearly 40% had concurrent rectal infection. 42 However, isolated extra-genital infections (without concurrent cervical infection) in women were not common in those studies, and the U.S. CDC does not recommend extra-genital screening for women.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…37, 38 The data on screening for women for extra-genital infection is mixed. Studies conducted in the 1970s and 1980s found that among women with genital tract infections with N. gonorrhoeae, approximately 10–25% had concurrent pharyngeal gonorrhea, 3336, 4042 and nearly 40% had concurrent rectal infection. 42 However, isolated extra-genital infections (without concurrent cervical infection) in women were not common in those studies, and the U.S. CDC does not recommend extra-genital screening for women.…”
Section: Screening and Diagnosismentioning
confidence: 99%